PENGARUH BIAYA PAKAN DAN TENAGA KERJA TERHADAP KEUNTUNGAN USAHA AYAM RAS PETELUR MILIK VONY KANAGA DI KELURAHAN TAWAAN KOTA BITUNG (Study kasus) - Tumion, Brian; Panelewen, V V.J; Makalew, A; Rorimpandey, B (Universitas Sam Ratulangi, 2017)
ABSTRACTEFFECT OF FEED AND OPERATING COSTS ON PROFIT OF CHICKEN LAYING FARM OWNED BY VONY KANAGA AT TAWAAN VILLAGE IN BITUNG CITY (Case study). This research was conducted in Vony Kanaga laying farm located in District Ranowulu Bitung City. The research problem was how the influence of feed and labor costs to the amount of profits and how much profit can be obtained at the company laying chicken farm in the district of Bitung City Ranowulu. The purpose of this study is to determine the effect of feed and labor costs against profits in laying chicken company, to find out the benefits of the company laying chicken farm in the district of Bitung City Ranowulu. The data collection method is using a field survey using primary and secondary data. Subdistrict Ranowulu Bitung determined based on the largest population in the city of Bitung. Model analysis of data that multiple linear regression analysis and profit. The measured variable is the cost of feed, labor costs and profits. The result showed that the average cost of laying chicken feed per day is Rp. 7.813.410. The average labor cost per day is Rp. 2.388.000. Total Proceeds from the sale of eggs and feces in the company-owned chicken laying Vony Kanaga Rp. 13.514.520 so as to obtain profit of Rp. 3.313.110. Based on the results of this study concluded that the cost of feed and labor simultaneously significant effect on profits in the company-owned farm chicken laying Vony Kanaga in District Ranowulu Bitung City. Company-owned farm chicken laying Vony Kanaga in District Ranowulu gives an average profit of Rp. 3.313.110Â Keywords: Feed Cost, Labor Cost, Pro